The Author in Middle Byzantine Literature : Modes, Functions, and Identities - Pizzone, Aglae (Byzantinisches Archiv., 2014)
Author and authorship have become increasingly important concepts in Byzantine literary studies. This volume provides the first comprehensive survey on strategies of authorship in Middle Byzantine literature and investigates the interaction between self-presentation and cultural production in a wide array of genres, providing new insights into how Byzantine intellectuals conceived of their own work and pursuits.